IS Attacks Southeast Asia During Ramadan - Gunaratna, Rohan (2016)
IS directed, instigated and inspired attacks in four continents including in Asia. In Malaysia, Philippines and Indonesia, where IS infrastructure is intact and growing, IS groups, cells and personalities mounted attacks during the holy month of Ramadan.